2019
DOI: 10.21608/ejh.2019.7317.1070
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Exposure To Wi-Fi Router Radiation On The Lung Of Adult Male Albino Rats: Histological And Immunohistochemical Study

Abstract: Introduction: Recent years have witnessed a marked increase in use of Wi-Fi devices in daily life. This new technology was approved to cause many health hazards. Aim of the Work: To investigate the histological structure changes occurred in the lung of the adult male albino rats after short and long time exposure of Wi-Fi router devices. Materials and Method: This study was carried out on 30 adult male albino rats. They were exposed to the 2.45 GHz radiation from Wi-Fi router device which was placed at 25 cm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The previous studies on the IF EMR up to 7.5 kHz to 150 kHz with different intensities have found no effect on the lung [53]. Radiofrequency exposure showed effects on the lung such as thickening of the alveolar wall and fibrosis and vascular congestion and lymphatic infiltration and inflammatory changes [54,55]. In the present study, the effect of EMR on the lungs need to be confirmed by repeating the work.…”
Section: Discussionmentioning
confidence: 50%
“…The previous studies on the IF EMR up to 7.5 kHz to 150 kHz with different intensities have found no effect on the lung [53]. Radiofrequency exposure showed effects on the lung such as thickening of the alveolar wall and fibrosis and vascular congestion and lymphatic infiltration and inflammatory changes [54,55]. In the present study, the effect of EMR on the lungs need to be confirmed by repeating the work.…”
Section: Discussionmentioning
confidence: 50%